1999
DOI: 10.1111/j.1651-2227.1999.tb01285.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimality of the birth population reduces learning and behaviour disorders and sudden infant death after the first month

Abstract: Saugstad LF. Optimality of the birth population reduces learning and behaviour disorders and sudden infant death after the first month. Acta Paediatr 1999; Suppl 429: 9-28. Stockholm. ISSN 0803-5326The weight distribution pattern of all births can be divided into a "skewing to the left" to lower weights and high neonatal mortality, a "skewing to the right" to higher weights (b3500 g) and minimum neonatal and postneonatal mortality, and a "symmetrical distribution" with mortality in between. This study was init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 113 publications
0
7
0
Order By: Relevance
“…First we examine fluctuations in cohort sizes, following the idea that systematic variation in cohort size leads one to suspect systematic changes in the composition. (For example, Saugstad, 1999, shows that in Denmark, changes in the composition of newborns go along with changes in birth rates.) Secondly, we discuss direct evidence on the composition.…”
Section: The Business Cycle At Birth Longevity and CV Mortalitymentioning
confidence: 99%
“…First we examine fluctuations in cohort sizes, following the idea that systematic variation in cohort size leads one to suspect systematic changes in the composition. (For example, Saugstad, 1999, shows that in Denmark, changes in the composition of newborns go along with changes in birth rates.) Secondly, we discuss direct evidence on the composition.…”
Section: The Business Cycle At Birth Longevity and CV Mortalitymentioning
confidence: 99%
“…3 Nonparametric estimates of the CV mortality rate by whether the cycle at birth is larger or smaller than 0 size leads one to suspect systematic changes in the composition. For example, Saugstad (1999) showed that in Denmark, changes in the composition of newborns go along with changes in birth rates. Second, we discuss direct evidence on the composition.…”
Section: Implications Of Ignored Heterogeneity Among Newborns and Evimentioning
confidence: 99%
“…SIDS birthweight averaged 200-300g lower than the sibs. Omega-3 levels in SIDS brainstems were lower than controls, it had been insufficiently provided in 3rd trimester (Saugstad, 1997b(Saugstad, , 1999b. Our common diet is deficient to such a degree that a deficit in Olfaction is common.…”
Section: Triggering Events In the Development Of Autismmentioning
confidence: 95%
“…The events have been known for decades, but mostly neglected. (13,56) What interests, is how to explain a pruning of SMA, an area in the Frontal Lobes, which is among the last to reach concurrence. To result in a persistent defect, the pruning needs to be very late and excessive in 2nd event in infancy, when axons and dendrites are pruned, resulting in a persistent defect.…”
Section: A Mother's Experience Of Her Autistic Infantmentioning
confidence: 99%